Specific knockdown of uPA/uPAR attenuates invasion in glioblastoma cells and xenografts by inhibition of cleavage and trafficking of Notch -1 receptor - Gujrati Meena; Dinh Dzung H; Gondi Christopher S; Raghu Hari; Rao Jasti S (Molecular Cancer, 2011)
Abstract Background uPA/uPAR is a multifunctional system that is over expressed in many cancers and plays a critical role in glioblastoma (GBM) invasion. Previous studies from our lab have also shown that uPA/uPAR down regulation inhibits cancer cell invasion in SNB 19 GBM cells. Methods As Notch 1 is known to be over expressed and promotes invasion in glioblastoma, we therefore tested our hypothesis of whether down regulation of uPA/uPAR, singly or in tandem, attenuates GBM invasion via Notch 1 receptor. Targeted down regulation of uPA/uPAR, either singly or simultaneously, inhibited the anchorage independent growth of U251MG and GBM xenograft cell lines 4910 and 5310 as assessed by soft agar colony formation assay. Expression of all four Notch receptors was confirmed in GBM tissue array analysis by immunohistochemistry. Results Down regulation of uPA/uPAR, either singly or simultaneously, in U251 MG and tumor xenografts inhibited the cleavage of the Notch receptor between the Gly 1743 and Val 1744 positions, thereby suggesting inhibition of activated cytosolic fragment-related Notch gene transcription. Morphological analysis confirmed inhibition of NICD when U251 MG cells were treated with puPA, puPAR or pU2. uPA/uPAR down regulation inhibited Notch 1 mRNA in all three examined cell lines. uPA/uPAR shRNA down regulated nuclear activation of NF-κB subunits and phosphorylation of AKT/mTOR pathway in U251 MG and GBM xenografts. puPA down regulated NICD and HES induced phosphorylation of AKT/ERK and NF-κB. Down regulation of Notch 1 using siRNA inhibited uPA activity as shown by fibrinogen zymography. It also decreased uPA expression levels as shown by western blotting. Exogenous addition of uPA activated Notch 1 in uPAR antisense U251 MG cells and also in uPAR antisense cells transfected with siRNA against Delta and Jagged. The Notch 1 receptor co-localized with LAMP-1, a marker for lysosomes in uPA, uPAR and U2, down regulated U251 MG cells which probably indicates inhibition of Notch 1 receptor trafficking in GBM cells. Notch 1 expression was significantly inhibited in puPA- and pU2-treated pre-established intracranial tumors in mice. Conclusions Overall our results show that down regulation of uPA/uPAR, either singly or simultaneously, could be an effective approach to attenuate Notch 1 receptor cleavage, signaling and endosomal trafficking in U251MG cells and xenografts, and ultimately inhibiting GBM invasion.